2017
DOI: 10.3389/fchem.2017.00066
|View full text |Cite
|
Sign up to set email alerts
|

New Insights about Antibiotic Production by Pseudomonas aeruginosa: A Gene Expression Analysis

Abstract: The bacterial resistance for antibiotics is one of the most important problems in public health and only a small number of new products are in development. Antagonistic microorganisms from soil are a promising source of new candidate molecules. Products of secondary metabolism confer adaptive advantages for their producer, in the competition for nutrients in the microbial community. The biosynthesis process of compounds with antibiotic activity is the key to optimize their production and the transcriptomic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The Fluopsin C was produced by P. aeruginosa LV strain (GenBank: QBLE00000000.1). These microorganisms were isolated from a citrus canker lesion on an orange ( Citrus sinensis cv.Valence) at Astorga, Paraná, Brazil (Gionco et al, 2017). The pathogens K. pneumoniae ATCC 10031 and Enterococcus faecium ATCC 6569 were used as susceptible strains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fluopsin C was produced by P. aeruginosa LV strain (GenBank: QBLE00000000.1). These microorganisms were isolated from a citrus canker lesion on an orange ( Citrus sinensis cv.Valence) at Astorga, Paraná, Brazil (Gionco et al, 2017). The pathogens K. pneumoniae ATCC 10031 and Enterococcus faecium ATCC 6569 were used as susceptible strains.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, our research group demonstrated the strong antibiotic activity of these semi-purified fractions against planktonic cells and biofilm formation of MDR isolates (Kerbauy et al, 2016). The gene expression analysis of P. aeruginosa LV strain showed that, when it is cultured in the presence of copper chloride, the bioremediation of intracellular excess copper forms a compound with high antimicrobial activity (Gionco et al, 2017). This bioactive compound was identified as a metalloantibiotic (organocopper compound), which is a great candidate for the development of new antibiotics to control infections caused by MRSA, CRE, VRE, and KPC-producing strains (Cardozo et al, 2013; Kerbauy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The development of metalloantibiotics as potential antimicrobial agents has been pursued since the 90s (Sekhon, 2010). The gene expression analysis of Pseudomonas aeruginosa LV strain cultured in the presence of copper chloride suggested that the intracellular excess of copper forms a compound with antimicrobial activity (Gionco et al, 2017). Other studies demonstrated that a specific fraction extracted from the supernatant of P. aeruginosa LV strain culture (F4A) presents high microbicidal activity against many pathogenic bacteria (de Oliveira et al, 2011Oliveira et al, , 2016Cardozo et al, 2013;Murate et al, 2015;Kerbauy et al, 2016;Munhoz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…protegens EMM-1 revealed an estimated molecular mass of 3 to 10 kDa. Although we cannot exclude the possibility that other inhibitory substances can be obtained by other methodologies as reported in other Pseudomonas species [ 54 , 55 ]. The inhibitory activity remained active at low pH and was not affected by heat treatment.…”
Section: Discussionmentioning
confidence: 99%